2018
DOI: 10.1016/j.energy.2018.05.093
|View full text |Cite
|
Sign up to set email alerts
|

Cooling energy simulation and analysis of an intermittent ventilation strategy under different climates

Abstract: This is the accepted version of a paper published in Energy. This paper has been peerreviewed but does not include the final publisher proof-corrections or journal pagination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Generally, IAJS has potential to offer an ambient temperature offset up to 2.5 ºC with an operational velocity of 0.4 m/s (using higher velocities increases the temperature offset), which is equivalent to 13% cooling demand reduction compared with MV. Cooling energy simulation and analysis under different climates demonstrate its feasibility and potential energy benefits (Kabanshi et al, 2018). IAJS as a primarysystem has potential application in climates where cooling is needed for most parts of the year as intermittent airflow, even at minimal operational velocity 0.4 m/s, was found undesirable below 23.7 ºC (Kabanshi et al, 2019).…”
Section: Periodic Variation Of the Ventilation Flowrate With A Sinementioning
confidence: 95%
“…Generally, IAJS has potential to offer an ambient temperature offset up to 2.5 ºC with an operational velocity of 0.4 m/s (using higher velocities increases the temperature offset), which is equivalent to 13% cooling demand reduction compared with MV. Cooling energy simulation and analysis under different climates demonstrate its feasibility and potential energy benefits (Kabanshi et al, 2018). IAJS as a primarysystem has potential application in climates where cooling is needed for most parts of the year as intermittent airflow, even at minimal operational velocity 0.4 m/s, was found undesirable below 23.7 ºC (Kabanshi et al, 2019).…”
Section: Periodic Variation Of the Ventilation Flowrate With A Sinementioning
confidence: 95%
“…Most building energy design has assumed that all rooms are occupied during operational hours to estimate maximum energy loads [14][15][16][17]. However, building occupancy rarely reaches the maximum load and always varies throughout the day in real life.…”
Section: Introductionmentioning
confidence: 99%
“…Based on their measurements they concluded that the system provided a more comfortable indoor thermal environment at elevated temperatures than was the case when conventional mixing and displacement ventilation systems were used. Kabanshi et al 9 also studied the effect of an IAJS, in which the supply provided air to the room with intermittent velocities between 0.4 m/s and 0.8 m/s, on cooling energy demand in different climates. Their results showed that the cooling energy demand could be significantly reduced by application of IAJS in hot and humid climates, while in hot and dry climates considerable energy savings could be achieved as well.…”
Section: Introductionmentioning
confidence: 99%
“…Kabanshi et al. 9 also studied the effect of an IAJS, in which the supply provided air to the room with intermittent velocities between 0.4 m/s and 0.8 m/s, on cooling energy demand in different climates. Their results showed that the cooling energy demand could be significantly reduced by application of IAJS in hot and humid climates, while in hot and dry climates considerable energy savings could be achieved as well.…”
Section: Introductionmentioning
confidence: 99%